A Review to Search Novel Antifungal Principles from Bioactive Plants: The Hidden Treasure (KYAMC Journal, 2022)
Now–a-days, fungal infections of the skin are very common in Bangladesh as like as the other countries in the world. Surprisingly, these infections have become very difficult to treat and cure permanently. We know that, skin takes part in many vital functions of the body as it is the largest organ. It maintains the temperature & salt-water balance and protects the internal organs from the external noxious environment. It is also involved in synthesis and excretion of many vital constituents of the body. Damage to the skin by various noxious stimuli like burns, injuries or infections are major concerns in Dermatology. At present, most of the health care providers in Bangladesh are facing serious problems due to the emergence of resistance to available anti-fungal drugs. The nature is considered as the hidden treasure of medicines. Innumerable natural compounds are used worldwide due to their acceptable margin of efficacy, safety & cost. The present review is involved to find out 24 (twenty four) bioactive plants used in rural Bangladesh as folklore medicines to treat various skin diseases including the fungal ones. Further researches are recommended immediately to identify, separate and assess the antifungal efficacy of bioactive principles present in these plants. Successful screening of the resistant fungal strains and their interaction with these bioactive compounds would also be an interesting era of study. Hopefully, the most promising compounds would be developed as newer medicines and manufactured commercially to combat the increasing burden of fungal epidemics.KYAMC Journal Vol. 13, No. 02, July 2022: 115-119